Designing health information technology tools to prevent gaps in public health insurance. Issue 2 (1st April 2017) - Hall, Jennifer D.; Harding, Rose L.; Angier, Heather; Likumahuwa-Ackman, Sonja; Cohen, Deborah J.; DeVoe, Jennifer E.; Gold, Rachel; Sumic, Aleksandra; Nelson, Christine A.
Abstract : Background: Changes in health insurance policies have increased coverage opportunities, but enrollees are required to annually reapply for benefits, which if not managed appropriately can lead to insurance gaps. Electronic health records (EHRs) can automate processes for assisting patients with health insurance enrollment and re-enrollment. Objective: We describe Community Health Centres' (CHCs') workflow, documentation, and tracking needs for assisting families with insurance application processes and the health information technology tool components that were developed to meet those needs. Method: We conducted a qualitative study using semi-structured interviews and observation of clinic operations and insurance application assistance processes. Data were analyzed using a grounded theory approach. We diagramed workflows and shared information with a team of developers who built the EHR-based tools. Results: Four steps to the insurance assistance workflow were common among CHCs: 1) identifying patients for public health insurance application assistance; 2) completing and submitting the public health insurance application when clinic staff met with patients to collect requisite information and helped them apply for benefits; 3) tracking public health insurance approval to monitor for decisions and 4) assisting with annual health insurance reapplication. We developed EHR-based tools to support clinical staff with each of these steps. Conclusion: CHCs are uniquely positioned to help patients and families with public health insurance applications. CHCs have invested in staff to assist patients with insurance applications and help prevent coverage gaps. To best assist patients and to foster efficiency, EHR-based insurance tools need comprehensive, timely, and accurate health insurance information.